Fenofibrate ameliorates diabetic retinopathy by modulating Nrf2 signaling and NLRP3 inflammasome activation - Liu, Qiuping; Zhang, Fengjun; Zhang, Xian; Cheng, Rui; Ma, Jian-xing; Yi, Jinglin; Li, Jingming (Molecular and cellular biochemistry, 2018)
Oxidative stress and neuroinflammation contribute significantly to the development and progression of diabetic retinopathy. Fenofibrate has received great attention as it benefits diabetic patients by reducing retinal laser requirement. Nuclear factor erythroid-2-related factor 2 (Nrf2) is a master regulator of anti-oxidative defense. Activation of nucleotide binding domain, leucine-rich repeat-containing receptor (NLR), pyrin domain-containing 3 (NLRP3) inflammasome plays a pivotal role in neuroinflammation. The purpose of this study is to determine whether fenofibrate protects retinas from oxidative damage and neuroinflammation via modulating the Nrf2 pathway and blocking NLRP3 inflammasome activation during diabetes. Diabetes is induced by intraperitoneal injection of streptozotocin in mice. Fenofibrate was given to mice in rodent chow. Upregulation of Nrf2 and NLRP3 inflammasome, enhanced ROS formation, and increased leukostasis and vascular leakage were observed in diabetic mouse retinas. Notably, Nrf2 and Caspase-1 were mainly colocalized with glutamine synthetase, one of the Mȕller cell markers. Fenofibrate further increased the expression of Nrf2 and its target gene NQO-1 and HO-1 and reduced ROS formation in diabetic retinas. In addition, retinal expression of NLRP3, Caspase-1 p20, IL-1β p17, and ICAM-1 were dramatically increased in vehicle-treated diabetic mice, which were abolished by fenofibrate intervention. Moreover, fenofibrate treatment also attenuated diabetes-induced retinal leukostasis and vascular leakage in mice. Taken together, fenofibrate attenuates oxidative stress and neuroinflammation in diabetic retinas, which is at least partially through modulating Nrf2 expression and NLRP3 inflammasome activation.